Correlation Between Risk of Febrile Neutropenia Based on Rondinelli Score with Clinical Outcomes in Acute Lymphoblastic Leukemia Patients - Alifadiningrat, Dianira Hanum Febia; Puspitasari, Dwiyanti; Hernaningsih, Yetti (Institute of Topical Disease Universitas Airlangga, 2022)
Febrile neutropenia (FN) is the most severe complication in patients with blood cancer and chemotherapy. Acute lymphoblastic leukemia (ALL) is the most common type of cancer in children and the most common cause of febrile neutropenia. The low number of neutrophils in ALL patients due to lymphoblast cancer cells and the toxicity of chemotherapy makes patients susceptible to infection which, if not treated immediately, can lead to death. Early risk assessment for infectious complications in FN patients is needed to increase clinician awareness in high-risk patients and eliminate unnecessary therapy for low-risk patients. The Rondinelli scoring system is a reasonably good instrument for predicting severe infectious complications in pediatric patients with ALL who have febrile neutropenia. This study aims to determine the relationship between the risk category for febrile neutropenia (FN) based on the Rondinelli score with clinical outcomes in FN patients with acute lymphoblastic leukemia (ALL) in the Hematology-Oncology division of the child health department of RSUD Dr. Soetomo. This analytic observational study used secondary data FN patients with acute lymphoblastic leukemia (ALL) implementing a total sampling. From 30 samples of pediatric ALL patients with febrile neutropenia at Dr. Soetomo Hospital for June 2018-June 2020 it was found 17 patients (56.7%) had a moderate risk score category, and 13 others were in a low-risk category (43.3 %). Patients were dominated by moderate and severe severity of neutropenia respectively, 43.3%, had neutropenia for 1-7 days (50%), fever less than seven days (66.7%), had a length of stay of 8-14 days, and 15-30 days 33.3% each. Conclusion from this research is that there was a signiï¬ cant relationship between the Rondinelli score category in pediatric ALL patients with FN with the severity of neutropenia p=0.037; R=0.383), duration of neutropenia (p=0.021; R=0.420), duration of fever (p=0.000; R=0.618), and length of stay (p-value 0.005; R=0.496).